Bacteriohopanepolyols and glycerol dialkyl glycerol tetraethers record redox regime shifts in a marine inlet in eastern Prydz Bay, Antarctica during the Holocene - Rush, Darci; van Kemenade, Zo (NIOZ, 2025)
Prydz Bay is located in the Southern Ocean, at the terminus of one of the largest glacial systems of East Antarctica. Consequently, its sedimentary record may hold information on the response of marine biogeochemical cycling to past and future changes in Antarctic oceanography. Bacteriohopanepolyols (BHPs) offer great potential to trace such changes, as these bacterial membrane lipids have been linked to distinct biogeochemical processes. Here, we present the BHP inventory of a Holocene sediment record, recovered from a marine basin in Eastern Prydz Bay. BHP lipidomics was combined with independent environmental proxies. Our results show elevated nucleoside-BHPs in early Holocene sediments from ~9.1 to 10.7 cal ka BP. As GDGT-based indices suggest terrestrial organic matter influx was insignificant, the presence of nucleoside-BHPs is interpreted to reflect autochthonous production under hypoxic-anoxic conditions, as inferred from BHT-x ratios ≥ 0.2. The record is characterized by a large diversity of rare and novel BHPs. Their occurrence is potentially related to membrane cold-adaptations of predominantly aerobic bacteria (i.e., TEX86OH-reconstructed sea surface temperatures are -2.4 to -0.8°C). Increased abundance and diversity of these BHPs between ~5.5– 7.5 and ~8.9– 9.8 cal ka BP is likely associated with an oxygenation of the basin at this time. The late Holocene (<3.0 cal ka BP) water column experienced photic zone euxinia, high rates of nitrogen loss and methanogenesis, as indicated by the presence of isorenieratene, enriched δ15N values and GDGT-0/cren ratios, respectively. BHPs in these sediments likely derive from two different ecological niches: i) the uppermost oxygenated waters where aerobic methane oxidation occurs and ii) the deeper sulfidic waters. This study shows that the Southern Ocean sedimentary record holds a diverse array of BHPs, including novel BHPs and BHPs formerly solely associated with terrestrial environments. BHPdistributions can be linked to distinct redox regime shifts within ...